Teks Tutur Jong Manten: Analisis Struktur dan Fungsi - Elviana Dewi, Desak Putu; Duana Sutika, I Nyoman; Ngurah Sulibra, I Ketut (Humanis; Volume 16. No. 1. Juli 2016, 2017)
The study regarding to the Text Tutur Jong Manten was aimed to analyze. The theory used in this study were the theory of structure and function proposed by Luxembrug, Teeuw, as Wellek&Warren. The methods used in this study were the method of literature, using qualitative methods and techniques used are recording techniques, and assisted with translation techniques. Techniques used are descriptive analytic and inductive, deductive thinking patterns. The result of the study revealed the structure and function of the Text Tutur Jong Manten. Conclusion from this analysis in structure from of the text is  language and style parable. Content structure were the beginning, content section, the and. The function of the text is to strengthen the trust and prohibition.
Keywords: text, narrative text, tutur, structure, function.